The effect of technology-assisted teaching on 10th forms students' listening comprehension: A quasi-experimantal study at Ngoc Hoi High School - Nguyen, Thi Bich (University of Languages and International Studies, 2017)
The effects that technology-assisted teaching may have on the comprehension of listening text by two groups 10th form students. Besides, the study also investigated the students’ opinions about the application of technology-assisted teaching on their liste (...)